Rejection of LGBT in the qur'an's view and sexual morality - Eko Budi Santoso; Roihan Sadad; Arif Prasetyo; Andi Rifka Afifah (At Turots: Jurnal Pendidikan Islam, 2025)
Lesbian, Gay, Bisexual and Transgender (LGBT) is a deviant phenomenon in the social environment, this occurs due to a lack of understanding of religion and the wise use of technology. The method used is qualitative analysis, where the data analyzed comes from primary sources such as information obtained from various electronic media and secondary sources such as journals, documents and news related to LGBT rejection. The results obtained show that society's values, religion and morality are incompatible with LGBT culture, giving rise to LGBT rejection movements in various regions in Indonesia. This deviation is a shared responsibility, both government, society, social institutions, educational institutions and youth organizations so that this can be minimized. Effective strategies to implement include implementing laws to have a deterrent effect, creating a positive environment, and supervising the younger generation. Focusing on LGBT rejection is important for Indonesian society to better understand the negative impacts it causes, both in terms of physical and mental health.